Fishbone Kerangka Pembuatan Peta Jalan (Roadmap) Badan Persandian - Pamungkas, R Wisnu Prio; Khalida, Rakhmi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
The coding Organization regulated in a government organization, requires a planning for the implementation of activities. Based on the pre-existing Grand Design or based on Principal Tasks and Functions of the positions of each organizational unit, it can be used as a form of making a Roadmap by making milestones the basis for implementation. Roadmap is used in the framework of a Fish Bone Diagram as a causal diagram, as well as with modern methodologies for using Project Management Life Cycles.